PROTOTYPE PINTU OTOMATIS MENGGUNAKAN SENSOR ULTRASONIK BERBASIS ARDUINO UNO - Erwin Darmawan (Jurnal Teknologi Komputer dan Informatika, 2025)
The development of automation systems continues to increase every year. One of them is the automation system on automatic doors. The use of human power in opening and closing the room door can be done automatically. Opening and closing the door can be done using electronic devices, making it easier to implement. In making this prototype, three main components are used, namely Ultrasonic Sensors, Arduino Uno Microcontrollers and Actuators in the form of servo motors. Ultrasonic sensors are used to detect the presence of humans who are about to go to the door, Servo Motors are used to open and close the door and the Microcontroller functions to process signals from ultrasonic sensors and provide output signals to the actuator. From the results of eight tests, In the entrance direction test, there were two failures out of eight tests.